Selected Papers from SDEWES 2018: Conferences on Sustainable Development of Energy, Water and Environment Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Preface Several countries have recently realized that the present paradigm of development in environmental and energy fields is unsustainable. As global awareness of environmental issues grows, governments worldwide are promoting policies which aim to limit the harmful effects of human development on the environment. In particular, these novel policies seek to address the rapid increase of the global temperature (especially in the polar regions) as well as to manage human plastic waste accumulating in seas. To resolve these issues will require a number of actions to be implemented; unfortunately, the recent COP 24 Conference was unsuccessful in establishing a global agreement to achieve these actions. In order for the upcoming 2020 COP 26 Conference to be successful in creating such an agreement, the scientific community must support the policymakers’ efforts. Within this framework, it is necessary to show the efforts of countries worldwide as they try to negotiate an agreement to increase the energy efficiency and reduce greenhouse gas (GHG) emissions. In addition, the research reports generated can provide quantitative measures of the necessary actions to be implemented in order to address sustainable and efficient energy use. Among other topics, the papers presented in this issue investigate innovations in novel efficient and environmentally friendly technologies mainly based on renewable energy sources. The study also highlights the different sectors involved in this task, such as energy conversion systems, urban areas, mobility, sustainability, water management, social aspects, etc. In this field, the Sustainable Development of Energy, Water and Environment Systems (SDEWES) conference provides the foremost forum for discussion on these topics. The 13th Sustainable Development of Energy, Water and Environment Systems Conference was held in Palermo, Italy in 2018. This Special Issue of Energies, precisely dedicated to 13th SDEWES Conference, features papers in three main topics: Energy policy and energy efficiency in urban areas, energy efficiency in industry, biomass and other miscellaneous energy systems.